2012
DOI: 10.1017/s0007114512004084
|View full text |Cite
|
Sign up to set email alerts
|

Immune factors and fatty acid composition in human milk from river/lake, coastal and inland regions of China

Abstract: Breast milk fatty acid composition may be affected by the maternal diet during gestation and lactation. The influence of dietary and breast milk fatty acids on breast milk immune factors is poorly defined. We determined the fatty acid composition and immune factor concentrations of breast milk from women residing in river/lake, coastal and inland regions of China, which differ in their consumption of lean fish and oily fish. Breast milk samples were collected on days 3 -5 (colostrum), 14 and 28 post-partum (PP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
21
3
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 58 publications
6
21
3
3
Order By: Relevance
“…BM contents of immune factors at the different lactation stages (Table 2) were also in agreement with the previously published ranges [18,48,49,50,51], as well as with our own previous findings (unpublished data), indicating that BM from Chinese mothers does not differ from worldwide references in these bioactive components.…”
Section: Discussionsupporting
confidence: 92%
“…BM contents of immune factors at the different lactation stages (Table 2) were also in agreement with the previously published ranges [18,48,49,50,51], as well as with our own previous findings (unpublished data), indicating that BM from Chinese mothers does not differ from worldwide references in these bioactive components.…”
Section: Discussionsupporting
confidence: 92%
“…From this study, it has been well-recognised that PA was the dominant SFA in human milk ( •78 %) were also main SFA but with much lower levels that were comparable to previous Chinese data (10,(21)(22)(23) . In our study, PA existed primarily at the sn-2 position with a rising tendency over lactation stages (74•65 % in CM, 75•60 % in TM, 80•75 % in MM).…”
Section: Sfasupporting
confidence: 90%
“…The MUFA in our study was comparable to Asian data (10,(21)(22)(23)(24)(25) but was much lower than Mediterranean studies (7,27) , mainly due to the lower level of OA (online Supplementary Table S1).…”
Section: Mufasupporting
confidence: 79%
“…A noteworthy exception being ARA (C20:4 n−6) with a value of only 0.48% in mature term HM in the current study vs. the range of 0.7 -1.1% reported by EFSA. Even the individual average contents of the included studies are consistently below the range reported by EFSA, with exception of three out of 38 studies [61][62][63]. This discrepancy seems to exemplify the value of a pooled data approach combining 38 studies to generate a representative ARA reference value in contrast to a single study selection as a base for the EFSA range [60,64].…”
Section: Discussionmentioning
confidence: 91%